Organizational psychology: application in the professional life - Elizalde, Rafael (2010)
This article attempts to provide insights into the importance of organizational psychology in the workplace and also how it can help resolve conflicts in the organization and supplemented with different professional fields. The authors, not psychologists, who enrolled in the final half of the Masters with a specialization in Organizational Psychology at UNMSM, expose the utility gives Organizational Psychology in their professional duties applied in the organization where they perform.